1977
DOI: 10.1002/1097-0142(197712)40:6<2836::aid-cncr2820400614>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A critical analysis of tumor morphology and hormone treatments in the untreated and estrogen-treated responsive and refractory human prostatic carcinoma

Abstract: This study was done to compare the ultrastructural features of prostatic cancer cells in both untreated and estrogen-treated responsive and refractory patients. Analysis of previously untreated and estrogen-treated carcinomas showed that the tumors possessed well-and poorly-differentiated acini, and invasive cells. Malignant acini contained numerous columnar (secretory) cells in untreated, but few in treated individuals. Two distinct types of basal cells were observed in untreated and treated acini: type I (li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…The average volumes on the day 21 were 75.7 ± 27.5 mm 3 for LNCaP/bcl‐2 and 8.0 ± 5.4 mm 3 for LNCaP/control ( P = 0.02). By day 35, however, the size of the tumors in all the mice had reached similar sizes of 101.8 ± 34.8 mm 3 and 128.5 ± 14.7 mm, 3 for LNCaP/bcl‐2 and LNCaP/control, respectively ( Fig. 4).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The average volumes on the day 21 were 75.7 ± 27.5 mm 3 for LNCaP/bcl‐2 and 8.0 ± 5.4 mm 3 for LNCaP/control ( P = 0.02). By day 35, however, the size of the tumors in all the mice had reached similar sizes of 101.8 ± 34.8 mm 3 and 128.5 ± 14.7 mm, 3 for LNCaP/bcl‐2 and LNCaP/control, respectively ( Fig. 4).…”
Section: Resultsmentioning
confidence: 90%
“…Prostate cancers generally show androgen‐dependent growth and undergo regression in response to androgen ablation by castration. 1,2 However, this treatment generally remains palliative and most eventually recur 3 and present androgen‐independent growth capacity as well as resistance to other treatment modalities, like chemotherapy. 4–6 It is now widely accepted that apoptosis, a genetically programmed process of autonomous cell death, is the mechanism of this regression and recurrent tumors develop anti‐apoptotic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Hormone ablation therapy has been a major treatment for prostate cancer for many years (Westin and Bergh, 1998). Although 70% of patients initially respond to this treatment, it is essentially palliative because, with time, almost all tumors will progress to an androgen independent state that is rapidly fatal (Sinha et al, 1977). An understanding of the molecular mechanisms that control this progression from hormone dependent to hormone independent is a key factor in the eective treatment of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Increased bcl-2 expression has also been associated with the progression of prostate cancer from androgen-dependent to androgen-independent growth (97). McDonnell et al (98) have suggested that the acquisition of an androgen-independent phenotype may be due to increased expression of bcl-2 because the majority of androgen-dependent tumors exhibited undetectable levels of the bcl-2 protein whereas the majority of androgen-independent prostate cancers tested exhibited high levels of bcl-2.…”
Section: Can the Existence Of The Apoptotic Pathway Indirectly Instigmentioning
confidence: 99%